2019
DOI: 10.1159/000495210
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Hippocampal Neuroimmune Response to Binge-Like Ethanol Consumption in the Drinking in the Dark Model

Abstract: Objectives: Alcohol dependence leads to dysregulation of the neuroimmune system, but the effects of excessive alcohol consumption on key players of the neuroimmune response after episodic binge drinking in nondependence has not been readily assessed. These studies seek to determine how the neuroimmune system within the hippocampus responds to binge-like consumption prior to dependence or evidence of brain damage. Methods: C57BL/6J mice underwent the drinking in the dark (DID) paradigm to recapitulate binge con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…In fact, this is the first report to indicate that non-dependent binge drinking increases GFAP immunoreactivity in the amygdala following the DID model (Figure 1). Our previous report found a similar response in the hippocampus with increased GFAP density after multiple cycles of DID ethanol exposure (Grifasi, McIntosh, et al, 2019). This finding agrees with the work of others who have shown that binge consumption in the DID model is associated with gene network expression changes that include astrocytic genes that regulate the neuroimmune response and glutamate synthesis (Mulligan et al, 2011).…”
Section: Non-dependent Binge Drinking Causes Astrogliosissupporting
confidence: 88%
See 2 more Smart Citations
“…In fact, this is the first report to indicate that non-dependent binge drinking increases GFAP immunoreactivity in the amygdala following the DID model (Figure 1). Our previous report found a similar response in the hippocampus with increased GFAP density after multiple cycles of DID ethanol exposure (Grifasi, McIntosh, et al, 2019). This finding agrees with the work of others who have shown that binge consumption in the DID model is associated with gene network expression changes that include astrocytic genes that regulate the neuroimmune response and glutamate synthesis (Mulligan et al, 2011).…”
Section: Non-dependent Binge Drinking Causes Astrogliosissupporting
confidence: 88%
“…The few studies on astrocytes and non-dependent alcohol consumption that are published focus on the effects that alcohol has on the astrocytes (Grifasi, McIntosh, et al, 2019;Mulligan et al, 2011), but this study also examined the effects of altered astrocyte function on alcohol consumption. The major findings of our study are as follows:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunoreactivity was measured with the open-source software Qupath 0.2.3 (University of Edinburg, Edinburg, UK) using experimenter-determined optical density thresholds [ 46 ]. Immunoreactivity is expressed as percent area (immunoreactive positive area/total area of ROI) [ 47 ]. Microglia were also assessed using profile cell counts of Iba-1 and are expressed as Iba-1+ cells/section [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative polymerase chain reaction (qRT-PCR) was performed similarly to our previous report [ 47 ]. Briefly, un-anesthetized mice were euthanized by rapid decapitation, and the hippocampus and amygdala were microdis-sected out and snap-frozen.…”
Section: Methodsmentioning
confidence: 99%